2014
DOI: 10.1108/ijse-06-2013-0149
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the welfare of sub-groups subject to premature mortality

Abstract: Purpose – The purpose of this paper is to provide an exposition of the concepts relevant to measuring the economic effect of premature mortality and the conception of how the social loss from premature mortality can be incorporated into social welfare measurement. None of the conventional welfare measures currently pick up this welfare signal. Design/methodology/approach – Various concepts are examined in the conventional and “new” liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…A set of studies showed fiscal decentralization has an effect on economic capacity, such as by Pitsvada and LoStracco (2002) and Elmassri et al (2016); yet, different findings are expressed by Ebdon et al (2016); Luehlfing (1996) and Bracci et al (2014), who indicated a non-significant relationship. The next research gap is the impact of fiscal decentralization against public welfare, for which Singh and Mahajan (2015) show significant and positive relationships, whereas Zulkhibri et al (2015); Raimi and Adeleke (2009); Salih (2003) and Doessel and Williams (2014) show contradicting results. This present study aims to fill the gap of previous studies, as well as to comprehensively examine the impact of fiscal decentralization toward good governance, economic capacity, and welfare.…”
Section: Introductionmentioning
confidence: 99%
“…A set of studies showed fiscal decentralization has an effect on economic capacity, such as by Pitsvada and LoStracco (2002) and Elmassri et al (2016); yet, different findings are expressed by Ebdon et al (2016); Luehlfing (1996) and Bracci et al (2014), who indicated a non-significant relationship. The next research gap is the impact of fiscal decentralization against public welfare, for which Singh and Mahajan (2015) show significant and positive relationships, whereas Zulkhibri et al (2015); Raimi and Adeleke (2009); Salih (2003) and Doessel and Williams (2014) show contradicting results. This present study aims to fill the gap of previous studies, as well as to comprehensively examine the impact of fiscal decentralization toward good governance, economic capacity, and welfare.…”
Section: Introductionmentioning
confidence: 99%